Release Profile of Losartan Potassium from Formulated Sustained Release Matrix Tablet (Bangladesh Pharmaceutical Journal, 2015)
The present study was undertaken to develop sustained release (SR) matrix tablets of Losartan potassium, an angiotensin-II antagonist for the treatment of hypertension. The tablets were prepared by direct compression method along with Kollidon SR and Methyl Cellulose as release retardant polymers. The evaluation involves two stages- the physical properties studies of tablets and in vitro release kinetics assessment. The USP paddle method was selected to perform the dissolution test and 900 ml phosphate buffer of pH 6.8 was used as dissolution medium at 50 rpm at 370C. The release kinetics were analyzed. All the formulations followed Higuchi release kinetics. When the release data was plotted into Korsmeyer-Peppas equation, then it was confirmed that F-1, F-2, F-3, F-4 and F-5 exhibited non-fickian type drug release whereas F-6 exhibited fickian type drug release from the tablet matrix. The in-vitro release studies revealed that the formulation F-2 can be taken as an ideal or optimized formulation of sustained release tablets for 24 hours release as it fulfills all the requirements for sustained release tablet. Furthermore, when the tablets were preheated at different temperature (300C, 450C, 600C) before dissolution they showed decrease in drug release compared with ambient temperature DOI: http://dx.doi.org/10.3329/bpj.v16i2.22301 Bangladesh Pharmaceutical Journal 16(2): 177-183, 2013